2018
DOI: 10.1080/23802359.2018.1535852
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of a rare diatom (Bacillariophyta) Proschkinia and its phylogenetic and taxonomic implications

Abstract: We obtained the complete mitogenome of Proschkinia sp. strain SZCZR1824, a strain belonging to a poorly known diatom genus with no previous molecular data. This genome is 48,863 bp long, with two group I introns in rnl and three group II introns in cox1. Using mitogenomic data, Proschkinia sp. was recovered with Fistulifera solaris, far distant from Navicula and Nitzschia, two genera with which Proschkinia has sometimes been associated based on morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…confirmed a close relationship of Proschkinia and Fistulifera as was previously indicated by Gastineau et al (2019), but with a much more diverse assemblage of taxa in the dataset, which might influence our interpretation of the resulting tree. For example, one may be tempted to draw conclusions about a potential homology between the fistula of Proschkinia and Fistulifera and the internally occluded stigma of Didymosphenia geminata, which was sister to the Proschkinia+Fistulifera clade in the dataset presented by Gastineau et al (2019). This, however, is not supported by our dataset with expanded taxon sampling.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…confirmed a close relationship of Proschkinia and Fistulifera as was previously indicated by Gastineau et al (2019), but with a much more diverse assemblage of taxa in the dataset, which might influence our interpretation of the resulting tree. For example, one may be tempted to draw conclusions about a potential homology between the fistula of Proschkinia and Fistulifera and the internally occluded stigma of Didymosphenia geminata, which was sister to the Proschkinia+Fistulifera clade in the dataset presented by Gastineau et al (2019). This, however, is not supported by our dataset with expanded taxon sampling.…”
Section: Discussionsupporting
confidence: 86%
“…Only very recently have the first molecular data on Proschkinia been provided. Gastineau et al (2019) sequenced the complete mitochondrial genome of one Proschkinia strain and compared the obtained results with available information on mitochondrial genes of other diatom taxa. According to the maximumlikelihood phylogenetic analysis performed, the examined strain of Proschkinia sp.…”
Section: Introductionmentioning
confidence: 99%
“…1), although informative, is not totally satisfying due to the low support at some of the nodes. Our results agree with Gastineau et al (2019) and Majewska et al (2019) in showing that Proschkinia is sister to Fistulifera. This pair also shares a clade with the genera Craticula, Sternimirus, Stauroneis, Parlibellus, Astartiella and Schizostauron, which agrees with the molecular phylogenies shown in Davidovich et al (2017) and Sabir et al (2018).…”
Section: Morphological Support For Molecular Clades?supporting
confidence: 93%
“…Round et al (1990) included this genus in the Proschkiniaceae, a monotypic family in the suborder Naviculineae, and Zgrundo et al (2013) noted the similarity of the fistula in Fistulifera to the isolated pore of Proschkinia, although they found no other evidence supporting a link between them and suggested that it was 'unlikely' that there was a close relationship. The genus has only recently been the subject of molecular phylogenetic studies (Gastineau et al 2019, Majewska et al 2019. Using a dataset of mitochondrial genes, Gastineau et al (2019) found Fistulifera and Proschkinia to be sister to one another and this has been confirmed by Majewska et (al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation